Pengaruh Persepsi Manfaat dan Kemudahan Penggunaan QRIS terhadap Keputusan Penggunaan GoPay Melalui Kepuasan Pengguna sebagai Interverning pada Mahasiswa: Studi pada Perguruan Tinggi Swasta di Kota Malang - Angga Eka Alfianto; Nasharuddin Mas; Alfiana Alfiana (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
Digital transformation in the payment system in Indonesia is experiencing rapid development, especially with the presence of the Quick Response Code Indonesian Standard (QRIS) which facilitates digital transactions in various sectors. One of the most popular digital wallet platforms and widely used by students is GoPay. This study aims to analyze the influence of the perception of benefits and ease of use of QRIS on GoPay usage decisions, with user satisfaction as an intervening or mediation variable. The research was conducted on students from private universities in Malang City using a quantitative approach with an explanatory design. A total of 73 respondents were selected using a simple random sampling technique and the data were analyzed using the Partial Least Square, method using the Technology Acceptance Model (TAM) theoretical framework as a theoretical foundation. The results of the analysis show that the ease of use of QRIS significantly affects students' decisions to use GoPay. This is indicated by a t-statistical value that exceeds the significance threshold of 1.96. However, the perception of benefits has not been shown to have a significant influence on usage decisions. In addition, the results of the mediation test showed that user satisfaction played a significant role as a mediator in the relationship between ease of use and GoPay usage decisions. In contrast, user satisfaction does not mediate the relationship between benefit perception and usage decisions. The implications of these findings emphasize the importance of developing a simple and intuitive user interface and user experience. Digital payment app developers are advised to focus on improving the usability aspect in order to encourage loyalty and repeat decisions from young users. This research makes an important contribution to the literature on the adoption of digital technology and the behavior of younger generation users in the era of digital transformation.